Atlas of multiplane transesophageal echocardiography - St. John Sutton, Martin; Maniet, Alan R (Martin Dunitz, 2003)
Clinically relevant emphasis here provides the reader with an authoritative review of what techniques are available and what images can be obtained. The multiplane probe, paediatric and 3D probes, and color flow Doppler are included.
Keywords: echokardiografie; Echocardiography, Transesophageal; kardiologie; radiologie, nukleární medicína a zobrazovací metody; Diagnostic Techniques, Cardiovascular; echokardiografie transezofageální; diagnostické techniky kardiovaskulární; ultrasonografie; Heart Diseases; Ultrasonography; Echocardiography; nemoci srdce